Peran Bank Syariah dalam Meningkatkan Kesejahteraan UMKM Masyarakat Desa Bungaraya (Studi Kasus: BSI KCP Siak, Kecamatan Siak, Kabupaten Siak, Provinsi Riau) - Julianingsih, Shally; Dewi, Sandra (ARZUSIN, 2026)
The role of Islamic banks in improving the welfare of micro, small, and medium enterprises (MSMEs) in rural communities has received attention in various studies, but research specifically examining the role of Islamic banks in the welfare of MSME actors in Bungaraya Village, Bungaraya Subdistrict, Siak Regency, Riau Province remains limited. This study aims to analyze the role of Islamic banks in improving the welfare of MSMEs in Bungaraya Village and to identify the barriers faced by the community in accessing Islamic banking services. This study used a qualitative approach with a case study design, involving 10 MSME informants selected through purposive sampling. Data were collected through observation, semi-structured interviews, documentation, and field notes, and were then analyzed using the interactive analysis technique of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results showed that Islamic banks play an important role in assisting business capital, increasing production capacity, and supporting the economic stability of MSME actors through sharia-based financing. In addition to providing economic benefits, Islamic banking services also provide a sense of security and peace of mind because transactions are carried out in accordance with Islamic principles. However, the use of Islamic banking services still faces barriers in the form of low Islamic financial literacy, limited access to services, minimal product socialization, and the public perception that sharia financing procedures are more complicated than those of conventional institutions. The conclusion of this study affirms that Islamic banks have a strategic role in supporting the welfare and economic empowerment of rural MSMEs. These findings contribute to the development of Islamic economics studies and sharia-based community empowerment, while also providing practical implications regarding the importance of strengthening Islamic financial literacy and inclusion among rural communities.